2011
DOI: 10.3233/jad-2010-100993
|View full text |Cite
|
Sign up to set email alerts
|

17α-Estradiol Attenuates Neuron Loss in Ovariectomized Dtg AβPP/PS1 Mice

Abstract: Quantitative microanalysis of brains from patients with Alzheimer's disease (AD) find neuronal loss and neuroinflammation in structures that control cognitive function. Though historically difficult to recapitulate in experimental models, several groups have recently reported that by middle-age, transgenic mice that co-express high levels of two AD-associated mutations, amyloid-β protein precursor (AβPPswe) and presenilin 1 (PS1ΔE9), undergo significant AD-type neuron loss in sub-cortical nuclei with heavy cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…The beneficial effects of 17α-E2 on Aβ levels were observed without the detrimental, superphysiological uterotrophic response observed following 17β-E2 treatment (Levin-Allerhand et al, 2002). Similarly, in estrogen-depleted APP SWE xPS1 mice, 17α-E2 attenuated the loss of neurons in CA1 and reduced microglial activation in the hippocampus (Manaye et al, 2011). When injected directly into the hippocampus of young, estrogen-depleted rats, the non-feminizing synthetic estrogen analogues, ZYC-5 and ZYC-13, increased cognitive performance to a similar extent as 17β-E2 (Walf et al, 2011), suggesting non-feminizing estrogens may have functional effects on memory in addition to their neuroprotective effects.…”
Section: In-vivo Evidence Of Neuroprotectionmentioning
confidence: 99%
“…The beneficial effects of 17α-E2 on Aβ levels were observed without the detrimental, superphysiological uterotrophic response observed following 17β-E2 treatment (Levin-Allerhand et al, 2002). Similarly, in estrogen-depleted APP SWE xPS1 mice, 17α-E2 attenuated the loss of neurons in CA1 and reduced microglial activation in the hippocampus (Manaye et al, 2011). When injected directly into the hippocampus of young, estrogen-depleted rats, the non-feminizing synthetic estrogen analogues, ZYC-5 and ZYC-13, increased cognitive performance to a similar extent as 17β-E2 (Walf et al, 2011), suggesting non-feminizing estrogens may have functional effects on memory in addition to their neuroprotective effects.…”
Section: In-vivo Evidence Of Neuroprotectionmentioning
confidence: 99%
“…To recapitulate the pathogenesis of human AD, APP23 mouse model overexpresses human APP with the Swedish mutation under the murine Thy1 promoter [ 57 ], while deltaE9 mice express APP with the Swedish mutation controlled by mouse prion protein promoter elements together with mutant human PS1 lacking exon 9, which is associated with familial AD [ 29 , 52 ]. Although these two transgenic mouse models display neuronal loss, cholinergic deficit, cognitive impairments, amyloid plaques and neuroinflammation in old age, the onsets of amyloid plaque formation and cognitive decline between them are very different in early adulthood [ 5 , 8 , 9 , 30 , 38 , 56 ]. Aβ deposits are not observed in APP23 mice younger than 6 months, but age-matched deltaE9 mice have already developed plaques [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, healthy brains do not appear to lose NE neurons during the natural aging process (Ohm et al, 1997). Manaye and colleagues (2011) described a neuroprotective role of estradiol in which this hormone attenuated the neuronal loss in the hypothalamus of ovariectomized rats in a rodent model of AD. Nonetheless, no studies have shown a neuroprotective effect of estradiol and progesterone in the LC, although there is evidence that the onset of menopause, characterized by the decline of ovarian steroids, can lead to anxiety and depression (Solomon & Herman, 2009; Warren, 2007), both related to alterations in NE neurotransmission.…”
Section: - Discussionmentioning
confidence: 99%